Upaya Mengembangkan Potensi Pariwisata Dan Penghijauan Waduk Di Desa Mojowono Kecamatan Kemlagi - Ratih Dwi Pangestu; Zulfa Muniroh; Rozy Nur Alif R.H; Syahril Dhiyah H.S; Luluk Maghfiroh; Devina Ayu P; Radika Novelia A.P; Yenny Triariani; Intan Dwi Utari; Poppy Nur Alifia P; Dyah Ayu K; Avivatin Khoirun N; Renggar Yudhistio S, M; Alfan Efendi; Rio Asrul Fa; Akhmad Ramadhan Yusga N; Bima Yogananta Adiansah; Rony Ad Wahyudy; Aan Nur Aris; Tegar Sukmawan; Rizal Dinar A.D; Risky Dwi P; Ismu Abdi S; Shela Novi Ana (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Mojowono Village is one of the villages in Kemlagi District, Mojokerto Regency, East Java Province which has local potential, namely agriculture, animal husbandry, MSMEs and tourism. Tourism potential in Mojowono Village can be developed because it has potential natural resources (SDA) and human resources (SDM). Tourism development activities aim to grow tourism businesses based on local potential in Mojowono Village, foster community creativity, and increase community economic resources. Tourism development is carried out through two programs, namely installing signboards between two reservoirs (Segawe Reservoir and Trunhyang Reservoir) in Mojowono village and environmental greening in the area around Segawe Reservoir. Implementation of the program involves the active role of the Mojowono Village Government and the community around the reservoir area. The installation of name signs at these two reservoirs has been able to attract tourists to visit Mojowono Village. However, there needs to be sustainability efforts through improving tourism infrastructure, increasing human resources for tourism managers and increasing tourism publications, promotions and branding so that Mojowono Village continues to develop as a tourist village in Kemlagi District.